To Study and Analyse the Customer Churn Prediction using Machine Learning Algorithm - Dr. Sonali Nemade; Dr. Sujata Patil; Mrs. Deepashree Mehendale; Mrs. Vidya Shinde; Mrs. Reshma Masurekar (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The customer churn prediction (CCP) is one of the challenging problems in the E-Commerce industry. With the advancement in the field of machine learning and artificial intelligence, the possibilities to predict customer churn has increased significantly. Our proposed methodology, consists of six phases. In the first two phases, data pre-processing and feature analysis is performed. In the third phase, feature selection is taken into consideration. Next, the data has been split into two parts train and test set in the ratio of 80% and 20% respectively. In the prediction process, most popular predictive models have been applied, namely, logistic regression, random forest classifier etc. on train set are applied to see the effect on accuracy of models. In addition, K-fold cross validation has been used over train set for hyper parameter tuning and to prevent overfitting of models. Finally, the obtained results on test set have been evaluated using confusion matrix and AUC curve.